Membangun City Branding Lokalitas dalam Tumbler Starbucks: Suatu Pendekatan Budaya - Gunawan Wiradharma (Universitas Medan Area, 2022)
This research aims to provide a comprehensive overview of how Tumbler Starbucks City Series Indonesia builds city branding on displayed cities. The method used in this study is qualitative with several supporting techniques such as library study techniques, listen, and record. The results of this study showed that the Tumbler Starbucks City Series can be said to